"Astronomical Heritage: Progressing the UNESCO– IAU Initiative". A Focus Meeting held at the 29th International Astronomical Union General Assembly, Honolulu, Hawai'i, 11th–13th August, 2015. (19th February 2016) - Saletta, Morgan
Abstract : .